Building a Responsive Legal System Through Reforming the Indonesian Constitution - Ndruru, Juliana; Kurnia, Kamal Fahmi (CV. Rayyan Dwi Bharata, 2024)
Legal politics or what is known as policy direction is important in order to provide direction on the form and material of law. However, in a study that examines the problems of law enforcement, in Indonesia, which was studied from a legal sociology perspective, it was stated that developments in the world today often give rise to various problems, whether in the form of violations of norms that exist in social life or rules that have a tendency to create a phenomenon that is contrary to moral and ethical rules as well as legal rules. This paper aims to find out the facts and legal political realities that occur on post-reform legislation in forming responsive laws. Using a normative writing method. The direction of legal politics in post-reform Indonesia is the desire to form a responsive legal system, this can be implicitly seen in several changes to the constitution. Change towards responsive law is not something instant and easy, there must be a commitment from the state and the people together to realize the ideal of this system. Although the current implementation of law still experiences many errors here and there, at least the existing legal products have led to laws that responsive, what is needed now are leadership figures who are able to bring Indonesia to the implementation of responsive laws that are in accordance with what was previously expected in order to achieve prosperity for the people.